Prevalence and associated factors of wheezing illnesses of children aged three to five years living in under-served settlements of the Colombo Municipal Council in Sri Lanka: a cross-sectional study - Ruwanika Seneviratne; Nalika S. Gunawardena (BMC, 2018)
Abstract Background A rising trend in Sri Lanka for asthma and wheezing illness is observed with higher morbidity in younger children and a paucity of related research. 'Under-served settlements' (USS) of Colombo Municipal Council (CMC) have poor living environments conducive to childhood wheezing. The objective was to describe the prevalence and associated factors of wheezing illnesses of three to five year old children living in low-income settlements in CMC. Methods A cross-sectional study was conducted on 460 three to five year old children and their caregivers using cluster sampling among residents of two randomly selected USSs of CMC. An interviewer-administered questionnaire, observation checklist and data extraction form were used in data collection. A physician's diagnosis of wheezing/whistling of the chest in their lifetime and a physician's diagnosis of wheezing/whistling within the past twelve months were considered as 'ever-wheezing illness' and 'current-wheezing illness' respectively. Results Mean age was 3.98 years (SD = ±0.64 years). A majority were males (51.3%) and Tamils (39.8%). Prevalence of 'ever wheezing illness' and 'current wheezing illness' were 38% (95% confidence interval (CI); 33.6%-42.5%) and 21.3% (95%CI; 17.6%-25.0%), respectively. Maternal (p < 0.001) and paternal (p < 0.001) histories of wheezing, playing with soft toys in the sleeping area (p = 0.004), place of cooking combined with the living area (p = 0.03), unsatisfactory ventilation in the sleeping area (p < 0.001) were found to be significantly associated with increased 'current wheezing' through multivariate analysis in this study. Use of formula milk before six months of age (p = 0.014) was found to be protective through multivariate analysis. Conclusions The magnitude of wheezing illnesses among three to five year old children residing in urban low-income settlements was found to be high. Children with a history of maternal and/or paternal wheezing should be targeted for early interventions to prevent wheezing illnesses. Interventions to avoid exacerbations should focus on the indoor environmental factors that were found to be associated with wheezing illnesses.